Design of open channels for non-Newtonian fluids - Rojas, DA; Janssen, RHA (Paste 2013: 16th International Seminar on Paste and Thickened Tailings, 2013)
The use of pipes for transporting non-Newtonian fluids has been widely studied and applied, and it can be said that a practical engineering level of knowledge and understanding has been reached for designing these types of systems. Useful design guides can be found for the design of pumped slurry systems. However, the scenario for open channels is different. Despite the fact that this topic has been studied by several investigators, it is difficult to find a clear explanation of the available methodology that establishes the steps necessary for designing non-Newtonian flow in open channels, delineating their range of application and presenting recommendations or comparisons as to which model would be better to use, depending on the particular application. To help present guidance for design engineers, a range of published experimental and operational results have been compiled from existing literature to allow categorisation of the different flow behaviours of non-Newtonian flows in open channels. Due to the nature of non-Newtonian flows, particularly those with yield stresses, there are analytical and practical limits for the dimensions of open channels. Analysis of the initiation of movement for slurries that exhibit a yield stress indicates that there are restrictions on the hydraulic radius to width ratios for open channels. Furthermore, since it is often desirable to operate industrial conduits transporting non-Newtonian slurries for stability and economic reasons near the transition from laminar to turbulent flow, it is important to accurately define the design of these channels near this transition point. The combination of the dimensional restrictions, together with the operational limits observed from the data, has been used to establish guidance for the dimensioning of open channels to convey non-Newtonian fluids. Following the proposed design guidelines, a sensitivity analysis has been performed to assess the impact of different rheological properties on the resulting open channel design. This paper will present the background to the analysis undertaken, the developed guidelines for open channel design, and the results of the sensitivity analysis.